Intensi Turnover Sebagai Mediasi Yang Mempengaruhi Komitmen Organisasi Terhadap Kepuasan Kerja Karyawan BBC - Yun Suprani; Yusro Hakimah; Muhammad Said (UNIVED Press, 2022)
The results of this study can be concluded as follows: 1. Organizational Commitment and Job Satisfaction have an effect on Employee Turnover. 2. Organizational Commitment is influenced by Job Satisfaction. Employees who feel a high level of job satisfaction will remain committed to the company. 3. Job satisfaction has a negative effect on employee turnover. Employees who are not dissatisfied with their work will do employee turnover. 4. Based on the results of the hypothesis test (t test), partially the Job Satisfaction variable and the Organizational Commitment variable have a significant effect on Employee Turnover. In addition, the negative direction of the variable Job Satisfaction and Organizational Commitment to Employee Turnover indicates that the higher Job Satisfaction and Organizational Commitment will affect the decrease in employee turnover, which means it has a good impact on the company. Vice versa if job satisfaction and organizational commitment are getting lower, it will have a negative impact on the company, which will affect the increase in employee turnover.